Morphological response of the smooth newt to water color and its dispersal in managed forest landscape - Männistö, Johannes (My University, 2024)
Amphibians are the most threatened group of vertebrates, facing multiple ecological stressors e.g. landscape degradation and habitat loss causing their rapid decline. Smooth newts (Lissotriton vulgaris) are semi-aquatic amphibians widely distributed in Europe. In landscapes newts have high demand of terrestrial and aquatic habitat types due to both habitats being essential to complete their life cycle. In boreal forests, forestry activities contribute to the decreasing number of wetlands, thus potentially affecting amphibian populations. In addition, water quality in the remaining wetlands is under multiple pressures: from eutrophication to the recently observed brownification phenomenon which is characterized by an increase in surface water color towards a yellow-brown hue. This latter process is mainly driven by increasing amount of dissolved organic matter (DOM) and dissolved iron (Fe) from terrestrial to aquatic environment and the declining deposit of atmospheric sulfur. Brownification has direct and indirect ecological effects on aquatic and semi-aquatic species. The attenuation of sunlight penetration by DOM affects e.g. primary production altering biological communities. While brownification may provide some benefits such as reducing harmful UV radiation, it can also pose challenges for species relying on visual cues, such as amphibians. Newts use visual cues for hunting and also in sexual selection. The effects of brownification to amphibians are not yet well understood, my thesis aims to partly fill up this gap of knowledge by investigating if the water color might drive morphological or colorimetric patterns of the smooth newts and addressing the effect of forest practices on newts dispersal. Data was gathered during summer 2023 in southern Finland. Passive sampling methods were used to trap smooth newts during the breeding season. Water color was measured at the different capture sites. The newts were brought to the laboratory to measure their morphological characteristics including size and colorimetric variables under anesthesia. The effects of forest practices were modeled by using MaxEnt and open-source data. Increase of water color was negatively correlated to Male newts Fulton index which indicates the newts body index. In addition, other responses varied between habitat types: male newts had less belly dots and also their tails hue peak wavelength in UV spectral range had positive relationship with water color in temporary wetlands but not in permanent. Whereas female newts belly hue in total spectral range had positive relationship with water color in temporary habitats but not in permanent. Forest age did not contribute towards newts dispersal. Thus, newts respond more towards water color in temporary wetlands emphasizing the importance of these unique habitats for newts morphological diversity. More research is needed to fully understand the effects of brownification, especially during the early development of newts in the breeding ponds.
Keywords: Amphibian, Water color, Temporary wetlands, Coniferous forest, Habitat quality